Proceedings of the 28th ACM International Conference on Multimedia 2020
DOI: 10.1145/3394171.3414444
|View full text |Cite
|
Sign up to set email alerts
|

Visual-speech Synthesis of Exaggerated Corrective Feedback

Abstract: To provide more discriminative feedback for the second language (L2) learners to better identify their mispronunciation, we propose a method for exaggerated visual-speech feedback in computerassisted pronunciation training (CAPT). The speech exaggeration is realized by an emphatic speech generation neural network based on Tacotron, while the visual exaggeration is accomplished by ADC Viseme Blending, namely increasing Amplitude of movement, extending the phone's Duration and enhancing the color Contrast. User … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Numerous studies have suggested that many L2 speech production (pronunciation) difficulties are rooted in perception [15,22,23,60,76]. Moreover, it has been exemplified that reinforcing the perception ability of learners can significantly contribute to the speech production ability automatically [4,8,43,44,70,80]. Exaggerated audiovisual feedback is a particular kind of perception reinforcement, which corrects the pronunciation by strengthening the user's visual or auditory attention.…”
Section: Learning Theoriesmentioning
confidence: 99%
“…Numerous studies have suggested that many L2 speech production (pronunciation) difficulties are rooted in perception [15,22,23,60,76]. Moreover, it has been exemplified that reinforcing the perception ability of learners can significantly contribute to the speech production ability automatically [4,8,43,44,70,80]. Exaggerated audiovisual feedback is a particular kind of perception reinforcement, which corrects the pronunciation by strengthening the user's visual or auditory attention.…”
Section: Learning Theoriesmentioning
confidence: 99%